2020
DOI: 10.1038/s41598-020-72797-8
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology based virtual screening of active constituents of Prunella vulgaris L. and the molecular mechanism against breast cancer

Abstract: Prunella vulgaris L, a perennial herb widely used in Asia in the treatment of various diseases including cancer. In vitro studies have demonstrated the therapeutic effect of Prunella vulgaris L. against breast cancer through multiple pathways. However, the nature of the biological mechanisms remains unclear. In this study, a Network pharmacology based approach was used to explore active constituents and potential molecular mechanisms of Prunella vulgaris L. for the treatment of breast cancer. The methods adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 47 publications
(59 reference statements)
1
40
0
Order By: Relevance
“…In recent studies carried out in our laboratory, we showed that dialkylphosphonomethylpropenenitriles 3, obtained from the Arbuzov reaction with Mannich base [12,22], (Scheme 1) behave as bilectrophilic agents [23,24]. Their double bond, strongly activated by the presence of the nitrile function and the phosphono group, easily adds nucleophiles [25].…”
Section: Results and Discussion Chemistrymentioning
confidence: 99%
“…In recent studies carried out in our laboratory, we showed that dialkylphosphonomethylpropenenitriles 3, obtained from the Arbuzov reaction with Mannich base [12,22], (Scheme 1) behave as bilectrophilic agents [23,24]. Their double bond, strongly activated by the presence of the nitrile function and the phosphono group, easily adds nucleophiles [25].…”
Section: Results and Discussion Chemistrymentioning
confidence: 99%
“…The compound-target-pathway network was constructed using Cytoscape 3.7.2. The topological properties were analysed using the Network Analyzer plug-in for Cytoscape to confirm the key components and targets 74 .…”
Section: Methodsmentioning
confidence: 99%
“…ChemBio Draw 3D and Autodock Tool were applied to optimize the structure of key compounds and targets, including 3-dimensional chemical structures creation, energy minimization, and format transformation 76 . PyMol was used to process the protein, including getting rid of the ligands, rectifying protein structure, and doing away with water 74 . Docking was completed by R 4.0.2 software and Autodock Vina, and the molecules with the lowest binding energy in the docking conformation were selected to observe the binding effect by matching with the original ligands and intermolecular interactions.…”
Section: Methodsmentioning
confidence: 99%
“…To further identify the tea flavonoids of each target, ADME was predicted based on molecular structure, which represents absorption, distribution, metabolism, and excretion 25 . Drug like (DL) and bioavailable score (BS) are a qualitative character to describe the physical and chemical properties of drugs and ADME properties 26 . 6 overlapping compounds from the top 10 tea flavonoids in each target also were illustrated.…”
Section: Identification Of the Key Tea Flavonoidsmentioning
confidence: 99%